Potential role of PAR2 inhibitors for treating rheumatoid arthritis - Fedorov, V. N.; Korsakov, M. K.; Khokhlov, A. L.; Arshinov, A. V.; Vdovichenko, V. P.; Leonova, O. V.; Suleymanov, S. Sh (Kachestvennai͡a︡ klinicheskai͡a︡ praktika, 2025)
Rheumatoid arthritis (RA) is a multifactorial incurable immune-inflammatory disease. Progression leads to joint deformation, cartilage and bone tissue destruction, and subsequent disability. The primary goal of RA pharmacotherapy is to achieve disease remission. For this purpose, several classes of drugs are used: basic anti-inflammatory drugs (DMARDs), which are a large group of synthetic and biological drugs that are combined according to their ability to influence the pathogenetic mechanisms of RA; glucocorticoids, which are recommended for use in combination with DMARDs; and non-steroidal anti-inflammatory drugs, which are used to relieve acute and chronic pain. The treatment of RA is a long-term process, and the drugs used for this condition are not always safe and not always effective, which leads to discontinuation of treatment in 20–50 % of patients. Therefore, there is a need to develop new pharmacological targets that can increase drug effectiveness and reduce drug toxicity. One promising therapeutic target is proteinase-activated receptors (PARs), particularly PAR2, whose activation contributes to the occurrence of inflammation, fibrosis, and proliferation of connective tissue. Experiments have demonstrated that inhibition of PAR2 activity prevents the development of RA pathogenesis and positively modifies the course of the disease. The search for drugs that inhibit PAR2 was carried out in the following directions: indirect blockade of PAR2 activity; creation of monoclonal antibodies; search for PAR2 inhibitors among peptide compounds; synthesis of low-molecular-weight inhibitory substances.